Post dural puncture headache (Journal of Institute of Medicine Nepal, 2011)
Introduction: Post dural puncture headache occurs as the cerebrospinal fluid leaks out from the breach that the needle has made in the dura. The incidence of Post Dural Puncture Headache (PDPH) is a common complication after spinal anesthesia. The objective of our study is to find out incidence of PDPH in patients undergoing surgery under spinal anesthesia in Dhulikhel Hospital. Methods: 120 patients who underwent spinal anesthesia were selected for the study. Questionnaire was used to assess the post dural puncture headache 24 hours after surgery. Headache, if present in frontal or occipital areas which increased when sitting or situational movement and relieves by lying in flat position were considered as PDPH. Results: PDPH was observed in 25% of the patients. The incidence of PDPH is 30% and 70% in male and female respectively. It was 2.33 times more in age group 18-30- years than 31-45 years. Conclusions: The incidence of PDPH was high in female and age group 18-30 years. The incidence of PDPH is high when the bevel is transverse to the dural fibers. Keywords: Bevel direction; incidence; post-dural puncture headache; spinal anesthesia   DOI: http://dx.doi.org/10.3126/joim.v32i2.4942 Journal of Institute of Medicine, August, 2010; 32: 30-32